The Swedish National Airway Register (SNAR): development, design and utility to date. Issue 1 (1st January 2020) - Stridsman, C; Konradsen, JR; Vanfleteren, L; Pedroletti, C; Binnmyr, J; Edfelt, P; Fjällman Schärberg, K; Sjöö, Y; Nyberg, F; Lindberg, A; Tunsäter, A; Ekberg-Jansson, A
ABSTRACT: Background: The Swedish National Airway Register (SNAR) was initiated in 2013 to ensure and improve the quality of care for patients with asthma and COPD. Aim: To describe the development and design of SNAR, and to study the 2019 data to evaluate its potential utility related to improvement of quality of care. Methods: SNAR includes data from patients with asthma (both children and adults) and COPD from primary, secondary and tertiary care, and also, for COPD inpatient care. Data on diagnostic investigations (e.g. spirometry, blood sample, skin prick test), symptom-scores, comorbidities and prescribed treatments are registered. The registrations are entered manually by healthcare professionals, or directly transferred from electronic medical records to a web-based platform. Results: In 2019, 1000 clinics participated and data were directly transferred by about 88% of them. The register included data on 205, 833 patients with asthma and 80, 372 with COPD (of these, 5% had both diagnoses). Registrations of new patients and follow-up visits from primary and secondary/tertiary care in 2019 were completed for 75, 707 patients with asthma (11, 818 children <12 yr, 6545 adolescents 12–17 yr, and 57, 344 adults >17 yr) and 38, 117 with COPD. Depending on age and disease group, 43–77% had performed spirometry, 36–65% Asthma Control Test, and 60% COPD Assessment Test. The prevalence of current smoking was about 2% in adolescents, 10% in adults with asthma, and 34% in COPD. For these, smoking cessation support was offered to 27%, 38% and 51%, respectively. Overall, limited data were available on investigation of allergy, 6-min walk test, patient education and written treatment plans. Regarding asthma, sex-differences in disease management were evident. Conclusion: SNAR has cumulatively registered data from over 270, 000 individuals, and the register is important for patients, caregivers, authorities, politicians and researchers to evaluate the effect of treatment and to ensure high and equal quality of care nationwide.